Characteristics and long-term health outcomes of the first domestic COVID-19 outbreak cases in Da Nang, Vietnam: a longitudinal cohort study - Miyuki Tsuruoka; Mai Kim Huynh; Michiko Toizumi; Thanh Tien Hoang; Trieu Bao Nguyen; Anh The Dao; Luong Dinh Nguyen; Huy Xuan Le; Chung Thanh Le; Anh Quang Dang; Hung Thai Do; Lay Myint Yoshida (Tropical Medicine and Health)
Abstract Background Vietnam experienced the first COVID-19 domestic outbreak due to the Wuhan strain (B.1.1) in Da Nang from July 2020. COVID-19 can cause acute as well as long-term health problems. We aimed to characterise clinical features and risk factors related to severe illness of COVID-19 among Da Nang outbreak cases and to describe long-term health outcomes among survivors of this outbreak. Methods We conducted an ambidirectional cohort study. Study subjects were all hospitalised cases with positive real-time PCR test of SARS-CoV-2 in the three major hospitals in Da Nang from 25 July to 28 August 2020. Clinical and demographic information was retrospectively collected from medical charts. Then, the survivors were followed-up prospectively at 6 and 16 months after acute infection to assess their health status via standardized questionnaires, physical examinations, chest X-rays and pulmonary function tests. Results A total of 362 cases including 20 fatal cases were enrolled into the study retrospectively. The median age of the participants included in the medical chart review was 46.5 years and 60.8% were female. Overall, 7.8% of the participants required respiratory support during hospitalisation and 20 of them died. Compared to the survivors, the fatal cases were significantly older (median age of survivors 45.0 yr vs fatal cases 66.5 yr, P < 0.001) and more likely to have underlying conditions. The proportions of participants who had at least one long COVID symptom within the 7 days of each follow-up at 6 and 16 months were 72.0% (134/186) and 63.5% (47/74), respectively. We also found that females and adults reported symptoms more often in the follow-up surveys, 78.9% (90/114) [females] vs 61.1% (44/72) [males] at 6 months, P = 0.008; 68.7% (46/67) [ $$\ge$$ ≥ 20 years] vs 14.3% (1/7) $$[<$$ [ < 20 years] at 16 months, P = 0.004. Conclusions In the first domestic COVID-19 outbreak in Vietnam, the mortality rate was approximately 6% and associated with underlying medical conditions. In the follow-up surveys, a substantial proportion of participants reported long COVID related health problems, although the prevalence declined over time. Females and adults reported symptoms more often, which might be due to the pathophysiological differences according to sex and age.